Yoga for essential hypertension: a systematic review. - Jie Wang; Xingjiang Xiong; Wei Liu (PLoS ONE, 2013)
Background Yoga is thought to be effective for health conditions. The article aims to assess the current clinical evidence of yoga for Essential hypertension (EH). Strategy MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials (CENTRAL) in the Cochrane Library were searched until June, 2013. We included randomized clinical trials testing yoga against conventional therapy, yoga versus no treatment, yoga combined with conventional therapy versus conventional therapy or conventional therapy combined with breath awareness. Study selection, data extraction, quality assessment, and data analyses were conducted according to the Cochrane standards. Results A total of 6 studies (involving 386 patients) were included. The methodological quality of the included trials was evaluated as generally low. A total of 6 RCTs met all the inclusion criteria. 4 of them compared yoga plus conventional therapy with conventional therapy. 1 RCT described yoga combined with conventional therapy versus conventional therapy combined with breath awareness. 2 RCT tested the effect of yoga versus conventional therapy alone. 1 RCT described yoga compared to no treatment. Only one trial reported adverse events without details, the safety of yoga is still uncertain. Conclusions There is some encouraging evidence of yoga for lowering SBP and DBP. However, due to low methodological quality of these identified trials, a definite conclusion about the efficacy and safety of yoga on EH cannot be drawn from this review. Therefore, further thorough investigation, large-scale, proper study designed, randomized trials of yoga for hypertension will be required to justify the effects reported here.